Father-child relations and the care of children with disabilities: the health team’s look (Research, Society and Development, 2021)
Objective: to describe the inclusion of the father figure in the care of children with disabilities. Methodology: this is a qualitative, exploratory and descriptive study. Data collection were carried out by means of interviews, with a semi structured questionnaire prepared by the main researcher, aimed at health professionals from a rehabilitation association. The analytical process took place by using Content Analysis. Results: nine health professionals participated and, after a detailed analysis of the data, the theme "The inclusion of the father in the care of the disabled child from the perspective of health professionals" emerged, and is composed of four categories: the figure of the main caregiver: reflection of the training process; the family configuration as a reference for the father's involvement in care; the sociocultural roles of maternal and paternal figures; and father figure as a reference in caring for children with disabilities. Final considerations: given the family adaptations in the event of having a child with a disability, the training of professionals lacks content that supports their performance for the inclusion of the father in the child's care.